Drying-free anti-cracking quick-drying wear-resistant pouring material and construction method

By modifying the main component of the casting material, quartz sand, and combining the use of titanium dioxide modified bauxite, cement composite materials and epoxy resin, the problems of large dry shrinkage value, low compressive strength and insufficient anti-seepage pressure of the casting material are solved, and efficient modification of the material is achieved, improving its compressive and impermeability properties.

CN119874389AActive Publication Date: 2025-04-25WUXI CITY YIGANG REFRACTORIES CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510129066.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-25
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

The existing casting materials have problems such as large dry shrinkage value, low compressive strength and insufficient permeability pressure, which affect their actual use.

Method used

By modifying the main component of the casting material, quartz sand, and combining the combined use of titanium dioxide modified bauxite, cement composite and epoxy resin, the drying shrinkage value is reduced, the compressive strength is increased, and the anti-seepage pressure is increased.

Benefits of technology

It effectively reduces the drying shrinkage value of the casting material, increases the compressive strength, and increases the permeability pressure, and improves the comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a drying-free anti-cracking quick-drying wear-resistant pouring material and a construction method. According to the invention, the main component quartz sand of the pouring material is modified, and the titanium dioxide modified bauxite, the cement composite material and the epoxy resin are used together, so that the drying shrinkage value of the pouring material is effectively reduced, the compressive strength is increased, and the anti-permeability pressure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a quick-drying, anti-explosion, wear-resistant casting material and a construction method thereof. Background Art

[0002] Casting material is a kind of granular and powdered material made of refractory substances, with a certain amount of binder and water added to it; casting material has high fluidity, is suitable for construction by pouring method, and is an amorphous refractory material that can be hardened without heating; casting material is mainly composed of refractory aggregate, powder, binder, admixture, water or other liquid materials, and is generally cast and formed at the site of use by pouring, vibration or tamping, and can also be made into prefabricated parts for use.

[0003] The Chinese patent (publication number CN118684476A) discloses a casting material and a preparation method thereof and an assembled casting forming large wall and a preparation method thereof. The invention groups and reorganizes the raw materials, treats the raw materials after small molecule treatment with high and low temperature, and then reorganizes with raw materials with strong chemical reaction ability, so as to achieve high adsorption of the raw materials; the special additives can produce mutual adsorption performance, which can greatly improve the strength of the raw materials; at the same time, the materials with strong chemical reaction ability are reorganized with ductile materials and wrapping materials to give the raw materials good flexibility, elasticity, memory and self-healing properties; in addition, the raw materials are compounded by multiple reorganizations, and the casting materials obtained have high strength, strong toughness, good ductility, high thermal insulation, high fire resistance and high corrosion resistance, and excellent comprehensive performance. However, the patent does not solve the problems of large drying shrinkage value, low compressive strength, and insufficient anti-seepage pressure existing in the casting materials in the prior art, which seriously affects its actual use.

[0004] Therefore, there is an urgent need for a quick-drying, anti-cracking, wear-resistant casting material and construction method that does not require drying. By modifying the composition of the casting material and selecting appropriate functional components, the drying shrinkage value can be reduced, the compressive strength can be increased, and the anti-seepage pressure can be improved. Summary of the invention

[0005] The purpose of the present invention is to provide a quick-drying, anti-cracking, wear-resistant casting material and a construction method that do not require drying. By modifying the main component of the casting material, quartz sand, and using it in combination with titanium dioxide-modified bauxite, cement composite materials and epoxy resin, the drying shrinkage value of the casting material can be effectively reduced, the compressive strength can be increased, and the anti-seepage pressure can be improved.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a quick-drying, anti-explosion, wear-resistant casting material that does not require drying. The casting material is made of the following raw materials in parts by weight: 40~50 parts of modified quartz sand, 20~30 parts of bauxite, 12~16 parts of gypsum, 10~14 parts of cement, 8~12 parts of epoxy resin, 2~4 parts of water reducing agent and 1~3 parts of defoaming agent; The preparation method of the modified quartz sand comprises: adding 10 to 20 parts of ferric nitrate to 90 to 100 parts of deionized water by weight to fully dissolve, then adding 40 to 50 parts of quartz sand and adjusting the pH to 9.2 to 9.6, stirring at a speed of 100 to 200 r / min for 4 to 6 hours, and after the stirring is completed, transferring to an oven and heating at 106 to 110° C. for 8 to 10 hours to obtain modified quartz sand.

[0007] Modified quartz sand introduces iron oxide, which can change the pore structure of the casting material matrix, making the pore distribution in the material more reasonable, which is beneficial to reduce the resistance on the water migration path and reduce the shrinkage stress generated during the drying process, thereby reducing the drying shrinkage value.

[0008] As a preferred solution, the bauxite is titanium dioxide modified bauxite; the preparation method of the titanium dioxide modified bauxite comprises: in parts by weight, 30 to 40 parts of bauxite, 12 to 20 parts of titanium dioxide, 6 to 10 parts of methyltrioctylammonium chloride, 2 to 6 parts of 2-methyl-2,4-pentanediol and 2 to 4 parts of polyethylene glycol are mixed evenly and then ball-milled for 24 to 30 hours to obtain a mixed slurry; the mixed slurry is heat-treated, cooled to room temperature after the heat treatment is completed, crushed, and ground to obtain titanium dioxide modified bauxite.

[0009] As a preferred solution, the heat treatment conditions include: the heat treatment temperature is 760-800°C, and the heat treatment time is 10-12h.

[0010] Due to the small size of titanium dioxide particles, titanium dioxide modified bauxite can act as a micro-filler in the casting material, filling the tiny gaps between the cement matrix and the aggregate to form a denser structure, reduce the generation and development of micro cracks, and thus improve the overall compressive strength.

[0011] As a preferred solution, the cement is a cement composite material; the preparation method of the cement composite material comprises: adding 2 to 4 parts of polyvinyl pyrrolidone to 100 to 110 parts of deionized water by weight and stirring evenly, then adding 4 to 8 parts of carboxylated graphene and ultrasonically dispersing for 50 to 60 minutes to obtain a graphene suspension; mixing 100 to 110 parts of the graphene suspension and 130 to 140 parts of sulphoaluminate cement for 6 to 8 minutes, drying, and crushing to obtain a cement composite material.

[0012] As a preferred scheme, the preparation method of the carboxylated graphene comprises: adding 2 to 6 parts of graphene oxide to 400 to 500 parts of deionized water by weight, ultrasonically dispersing for 50 to 60 minutes, then adding 6 to 10 parts of sodium hydroxide and 16 to 20 parts of azobisisobutyronitrile and ultrasonically dispersing for 30 to 40 minutes, reacting at 30 to 34° C. for 4 to 6 hours, washing with water, and drying to obtain carboxylated graphene.

[0013] As a preferred solution, the particle size of the sulphoaluminate cement is 20-200 μm.

[0014] Cement composites are modified by introducing carboxylated graphene. The carboxyl functional group can react chemically with calcium ions in the hydration products of the casting materials to form stable chemical bonds, thereby enhancing the interfacial bonding between the cement and the matrix and promoting the formation of a denser microstructure, thereby reducing the penetration path of water and other harmful substances, effectively preventing them from entering the interior of the material, and improving the material's anti-seepage pressure.

[0015] As a preferred solution, the epoxy resin is bisphenol A epoxy resin and phenol novolac epoxy resin; the mass ratio of the bisphenol A epoxy resin to the phenol novolac epoxy resin is (1~2):1.

[0016] By using bisphenol A epoxy resin and phenol novolac epoxy resin together and controlling the mass ratio of the two, a good compounding effect can be achieved. It acts as a binder for the modified components, effectively reducing the drying shrinkage value of the casting material, increasing the compressive strength, and at the same time improving the anti-seepage pressure.

[0017] As a preferred solution, the water reducer is selected from any one of polycarboxylate water reducer, melamine water reducer and naphthalene water reducer or a combination of at least two thereof.

[0018] As a preferred solution, the defoaming agent is selected from any one of tributyl phosphate, polydimethylsiloxane, and triglycerol monostearate, or a combination of at least two thereof.

[0019] The second aspect of the present invention provides a construction method for a quick-drying wear-resistant casting material that does not require drying and is resistant to cracking. The quick-drying wear-resistant casting material that does not require drying and is resistant to cracking as described in the first aspect is mixed with water, stirred thoroughly and evenly, and then spread on the construction surface and compacted, ground and polished.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention introduces epoxy resin into the casting material. The epoxy group of the epoxy resin can react with the carboxyl group in the cement composite material. At the same time, through the compounding of bisphenol A epoxy resin and phenol novolac epoxy resin, it effectively acts as a binder for modified quartz sand and titanium dioxide modified bauxite, thereby constructing a network interconnected structure, effectively limiting the drying shrinkage of the casting material, and at the same time increasing the compressive strength and improving the anti-seepage pressure.

[0021] 2. The modified quartz sand of the present invention introduces iron oxide, which can change the pore structure of the casting material matrix, making the pore distribution in the material more reasonable, which is beneficial to reduce the resistance on the water migration path and reduce the shrinkage stress generated during the drying process, thereby reducing the drying shrinkage value.

[0022] 3. Due to the small size of titanium dioxide particles, the titanium dioxide modified bauxite of the present invention can act as a micro-filler in the casting material, filling the tiny gaps between the cement matrix and the aggregate to form a denser structure, reduce the generation and development of micro cracks, and thus improve the overall compressive strength.

[0023] 4. The cement composite material of the present invention introduces carboxylated graphene through modification. The carboxyl functional group can react chemically with calcium ions in the hydration product of the casting material to form a stable chemical bond, thereby enhancing the interfacial bonding force between the cement and the matrix and promoting the formation of a denser microstructure, thereby reducing the penetration path of water and other harmful substances, effectively preventing them from entering the interior of the material, and improving the material's anti-seepage pressure. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The sources of some components in the embodiments and comparative examples are as follows: Quartz sand, item number sjz139, was purchased from Shijiazhuang Tourmaline Mineral Products Co., Ltd.; Ferric nitrate, CAS No. 7782-61-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Bauxite, model YY-75, purchased from Gongyi Yuying Refractory Material Co., Ltd.; Gypsum, brand 20140, purchased from Weifang Shengchuan Chemical Co., Ltd.; Sulphoaluminate cement I, with an average particle size of 20 μm, was purchased from Sanxiang Special Cement Company; Sulphoaluminate cement II, with an average particle size of 4 mm, was purchased from Hubei Yicheng Anda Special Cement Co., Ltd.; Bisphenol A epoxy resin, product number XHL1920, purchased from Hubei Xinhongli Chemical Co., Ltd.; Phenol novolac epoxy resin, model SQPN-051, purchased from Shandong Shengquan New Materials Co., Ltd.; Polycarboxylate water reducer, model ZWL-A-Ⅸ, purchased from Zhejiang Wulong Chemical Co., Ltd.; Melamine water reducing agent, model VF-8, purchased from Shanghai Luke Chemical Co., Ltd.; Naphthalene-based water reducer, model SNF-A, purchased from Shenyang Xingzhenghe Chemical Co., Ltd.; Tributyl phosphate, CAS No. 126-73-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Polydimethylsiloxane, CAS No. 9006-65-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Triglycerol monostearate, CAS No. 26855-43-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Titanium dioxide, CAS No. 13463-67-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Methyltrioctylammonium chloride, CAS No. 63393-96-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.; 2-Methyl-2,4-pentanediol, CAS No. 107-41-5, purchased from Sinopharm Chemical Reagent Co., Ltd.; Polyethylene glycol, product number P103725, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Graphene oxide, model DN-20DY, was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. Azobisisobutyronitrile, CAS No. 78-67-1, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Polyvinyl pyrrolidone, product number S30267, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0026] Example 1 This embodiment provides a quick-drying, anti-explosion, wear-resistant casting material that does not require drying. The casting material is made of the following raw materials in parts by weight: 50 parts of modified quartz sand, 30 parts of titanium dioxide modified bauxite, 16 parts of gypsum, 14 parts of cement composite material, 12 parts of epoxy resin (8 parts of bisphenol A epoxy resin and 4 parts of phenol novolac epoxy resin), 2-4 parts of polycarboxylic acid water reducer and 1-3 parts of defoaming agent tributyl phosphate; Preparation of the modified quartz sand: by weight, 20 parts of ferric nitrate are added to 100 parts of deionized water to fully dissolve, then 50 parts of quartz sand are added and the pH is adjusted to 9.6, stirred at a speed of 200 r / min for 4 hours, and after the stirring is completed, transferred to an oven and heated at 110° C. for 8 hours to obtain modified quartz sand; Preparation of the titanium dioxide modified bauxite: by weight, 40 parts of bauxite, 20 parts of titanium dioxide, 10 parts of methyl trioctyl ammonium chloride, 6 parts of 2-methyl-2,4-pentanediol and 4 parts of polyethylene glycol are mixed evenly and then ball-milled for 30 hours to obtain a mixed slurry; the mixed slurry is heat-treated (heat treatment temperature is 800° C., heat treatment time is 10 hours), cooled to room temperature after the heat treatment is completed, crushed, and ground to obtain titanium dioxide modified bauxite; Preparation of the cement composite material: (1) by weight, 6 parts of graphene oxide are added to 500 parts of deionized water, ultrasonically dispersed for 60 minutes, then 10 parts of sodium hydroxide and 20 parts of azobisisobutyronitrile are added and ultrasonically dispersed for 40 minutes, reacted at 34°C for 4 hours, washed with water, and dried to obtain carboxylated graphene. (2) by weight, 4 parts of polyvinyl pyrrolidone are added to 110 parts of deionized water and stirred evenly, then 8 parts of carboxylated graphene are added and ultrasonically dispersed for 60 minutes to obtain a graphene suspension; 110 parts of the graphene suspension and 140 parts of sulphoaluminate cement I (average particle size of 20 μm) are mixed and stirred for 8 minutes, dried, and crushed to obtain a cement composite material.

[0027] Example 2 This embodiment provides a quick-drying, anti-explosion, wear-resistant casting material that does not require drying. The casting material is made of the following raw materials in parts by weight: 40 parts of modified quartz sand, 20 parts of titanium dioxide modified bauxite, 12 parts of gypsum, 10 parts of cement composite material, 8 parts of epoxy resin (4 parts of bisphenol A epoxy resin and 4 parts of phenol novolac epoxy resin), 2 parts of melamine water reducer and 1 part of defoaming agent polydimethylsiloxane; Preparation of the modified quartz sand: by weight, 10 parts of ferric nitrate are added to 90 parts of deionized water to fully dissolve, then 40 parts of quartz sand are added and the pH is adjusted to 9.2, stirred at a speed of 100 r / min for 6 hours, and after the stirring is completed, transferred to an oven and heated at 106° C. for 10 hours to obtain modified quartz sand; Preparation of the titanium dioxide modified bauxite: by weight, 30 parts of bauxite, 12 parts of titanium dioxide, 6 parts of methyl trioctyl ammonium chloride, 2 parts of 2-methyl-2,4-pentanediol and 2 parts of polyethylene glycol are mixed evenly and then ball-milled for 24 hours to obtain a mixed slurry; the mixed slurry is heat-treated (heat treatment temperature is 760° C., heat treatment time is 12 hours), cooled to room temperature after the heat treatment is completed, crushed, and ground to obtain titanium dioxide modified bauxite; The preparation method of cement composite material comprises: (1) adding 2 parts of graphene oxide to 400 parts of deionized water by weight, ultrasonically dispersing for 50 minutes, then adding 6 parts of sodium hydroxide and 16 parts of azobisisobutyronitrile and ultrasonically dispersing for 30 minutes, reacting at 30°C for 6 hours, washing with water, and drying to obtain carboxylated graphene. (2) adding 2 parts of polyvinyl pyrrolidone to 100 parts of deionized water by weight and stirring evenly, then adding 4 parts of carboxylated graphene and ultrasonically dispersing for 50 minutes to obtain graphene suspension; mixing 100 parts of the graphene suspension and 130 parts of sulphoaluminate cement I (average particle size of 20 μm) and stirring for 6 minutes, drying, and crushing to obtain cement composite material.

[0028] Example 3 This embodiment provides a quick-drying, anti-explosion, wear-resistant casting material that does not require drying. The casting material is made of the following raw materials in parts by weight: 45 parts of modified quartz sand, 25 parts of titanium dioxide modified bauxite, 14 parts of gypsum, 12 parts of cement composite material, 10 parts of epoxy resin (6 parts of bisphenol A epoxy resin and 4 parts of phenol novolac epoxy resin), 3 parts of naphthalene series water reducer and 2 parts of defoaming agent tripolyglycerol monostearate; Preparation of the modified quartz sand: by weight, 15 parts of ferric nitrate are added to 95 parts of deionized water to fully dissolve, then 45 parts of quartz sand are added and the pH is adjusted to 9.4, stirred at a speed of 150 r / min for 5 hours, and after the stirring is completed, transferred to an oven and heated at 108° C. for 9 hours to obtain modified quartz sand; Preparation of the titanium dioxide modified bauxite: by weight, 35 parts of bauxite, 16 parts of titanium dioxide, 8 parts of methyl trioctyl ammonium chloride, 4 parts of 2-methyl-2,4-pentanediol and 3 parts of polyethylene glycol are mixed evenly and then ball-milled for 26 hours to obtain a mixed slurry; the mixed slurry is heat-treated (heat treatment temperature is 780° C., heat treatment time is 11 hours), cooled to room temperature after the heat treatment is completed, crushed, and ground to obtain titanium dioxide modified bauxite; The preparation method of cement composite material comprises: (1) adding 4 parts of graphene oxide to 450 parts of deionized water by weight, ultrasonically dispersing for 55 minutes, then adding 8 parts of sodium hydroxide and 18 parts of azobisisobutyronitrile and ultrasonically dispersing for 35 minutes, reacting at 32°C for 5 hours, washing with water, and drying to obtain carboxylated graphene. (2) adding 3 parts of polyvinyl pyrrolidone to 105 parts of deionized water by weight and stirring evenly, then adding 6 parts of carboxylated graphene and ultrasonically dispersing for 56 minutes to obtain graphene suspension; mixing 105 parts of the graphene suspension and 135 parts of sulphoaluminate cement I (average particle size of 20 μm) for 7 minutes, drying, and crushing to obtain cement composite material.

[0029] Comparative Example 1 The difference between this comparative example and Example 1 is that commercially available quartz sand is used instead of modified quartz sand.

[0030] Comparative Example 2 The difference between this comparative example and Example 1 is that commercially available bauxite is used instead of titanium dioxide modified bauxite.

[0031] Comparative Example 3 The difference between this comparative example and Example 1 is that sulphoaluminate cement I is used to replace the cement composite material.

[0032] Comparative Example 4 The difference between this comparative example and Example 1 is that sulphoaluminate cement II is used instead of sulphoaluminate cement I to prepare the cement composite material.

[0033] Comparative Example 5 The difference between this comparative example and Example 1 is that the amount of bisphenol A epoxy resin is changed to 10 parts, and the amount of phenol novolac epoxy resin is changed to 2 parts.

[0034] Comparative Example 6 The difference between this comparative example and Example 1 is that the amount of bisphenol A epoxy resin is changed to 4 parts, and the amount of phenol novolac epoxy resin is changed to 8 parts.

[0035] Performance Testing The casting materials of the above-mentioned embodiments and comparative examples were subjected to the following tests: (1) Drying shrinkage test: The test shall be conducted in accordance with the requirements of GB / T 29417-2012 Test method for drying shrinkage and cracking performance of cement mortar and concrete.

[0036] (2) Compressive strength test: Test according to the requirements of GB / T 50081-2019 Standard for Test Methods for Physical and Mechanical Properties of Concrete.

[0037] (3) Anti-seepage performance test: Test in accordance with the requirements of GB 18445-2012 Cement-based penetrating crystalline waterproof materials.

[0038] Table 1 Performance test results

[0039] It can be seen from the above performance test results that the casting materials of Examples 1-3 have the best comprehensive performance, with a drying shrinkage value of 1.1~1.5mm / m, a 28d compressive strength of 36.5~37.2MPa, and a water-resistance pressure of 1.9~2.2MPa; this is mainly because the main component of the casting material, quartz sand, is modified and used in conjunction with titanium dioxide-modified bauxite, cement composite materials and epoxy resin, which effectively reduces the drying shrinkage value of the casting material, increases the compressive strength, and improves the water-resistance pressure.

[0040] The comparative example did not adopt the necessary technical solution, resulting in that it was significantly worse than the embodiment in the corresponding performance test; compared with Example 1, the comparative example 1 used commercially available quartz sand instead of modified quartz sand, and the drying shrinkage value became larger, the compressive strength decreased, and the anti-seepage pressure decreased; compared with Example 1, the comparative example 2 used commercially available bauxite instead of titanium dioxide modified bauxite, and the drying shrinkage value became larger, the compressive strength decreased, and the anti-seepage pressure decreased; compared with Example 1, the comparative example 3 used sulfoaluminate cement I instead of cement composite material, and the drying shrinkage value became larger, the compressive strength decreased, and the anti-seepage pressure decreased; compared with Example 1, the comparative example 4 used sulfoaluminate cement II instead of sulfoaluminate cement I for cement Preparation of composite materials, due to the large particle size of sulphoaluminate cement II, the modification effect is not good, the drying shrinkage value becomes larger, the compressive strength decreases, and the anti-seepage pressure decreases; compared with Example 1, the amount of bisphenol A epoxy resin in Comparative Example 5 is changed to 10 parts, and the amount of phenol novolac epoxy resin is changed to 2 parts. Due to the excessive amount of bisphenol A epoxy resin, the compounding effect is not good, the drying shrinkage value becomes larger, the compressive strength decreases, and the anti-seepage pressure decreases; compared with Example 1, the amount of bisphenol A epoxy resin in Comparative Example 6 is changed to 4 parts, and the amount of phenol novolac epoxy resin is changed to 8 parts. Due to the small amount of bisphenol A epoxy resin, the compounding effect is not good, the drying shrinkage value becomes larger, the compressive strength decreases, and the anti-seepage pressure decreases. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.

[0041] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A quick-drying, anti-explosion, wear-resistant casting material that does not require drying, characterized in that: The casting material is made of the following raw materials in parts by weight: 40~50 parts of modified quartz sand, 20~30 parts of bauxite, 12~16 parts of gypsum, 10~14 parts of cement, 8~12 parts of epoxy resin, 2~4 parts of water reducing agent and 1~3 parts of defoaming agent; The preparation method of the modified quartz sand comprises: adding 10 to 20 parts of ferric nitrate to 90 to 100 parts of deionized water by weight to fully dissolve, then adding 40 to 50 parts of quartz sand and adjusting the pH to 9.2 to 9.6, stirring at a speed of 100 to 200 r / min for 4 to 6 hours, and after the stirring is completed, transferring to an oven and heating at 106 to 110° C. for 8 to 10 hours to obtain modified quartz sand.

2. The quick-drying, anti-explosion, wear-resistant casting material according to claim 1, characterized in that: The bauxite is titanium dioxide modified bauxite; The preparation method of the titanium dioxide modified bauxite comprises: in parts by weight, 30 to 40 parts of bauxite, 12 to 20 parts of titanium dioxide, 6 to 10 parts of methyl trioctyl ammonium chloride, 2 to 6 parts of 2-methyl-2,4-pentanediol and 2 to 4 parts of polyethylene glycol are uniformly mixed and then ball-milled for 24 to 30 hours to obtain a mixed slurry; the mixed slurry is heat-treated, cooled to room temperature after the heat treatment is completed, crushed and ground to obtain the titanium dioxide modified bauxite.

3. The quick-drying, anti-explosion, wear-resistant casting material according to claim 2, characterized in that: The heat treatment conditions include: a heat treatment temperature of 760-800° C. and a heat treatment time of 10-12 hours.

4. The quick-drying, anti-explosion, wear-resistant casting material according to claim 1, characterized in that: The cement is a cement composite material; The preparation method of the cement composite material comprises: adding 2 to 4 parts of polyvinyl pyrrolidone to 100 to 110 parts of deionized water by weight and stirring evenly, then adding 4 to 8 parts of carboxylated graphene and ultrasonically dispersing for 50 to 60 minutes to obtain a graphene suspension; mixing 100 to 110 parts of the graphene suspension and 130 to 140 parts of sulphoaluminate cement for 6 to 8 minutes, drying, and crushing to obtain a cement composite material.

5. The quick-drying, anti-explosion, wear-resistant casting material according to claim 4, characterized in that: The preparation method of the carboxylated graphene comprises: adding 2 to 6 parts of graphene oxide to 400 to 500 parts of deionized water by weight, ultrasonically dispersing for 50 to 60 minutes, then adding 6 to 10 parts of sodium hydroxide and 16 to 20 parts of azobisisobutyronitrile and ultrasonically dispersing for 30 to 40 minutes, reacting at 30 to 34° C. for 4 to 6 hours, washing with water, and drying to obtain the carboxylated graphene.

6. The quick-drying, anti-explosion, wear-resistant casting material according to claim 4, characterized in that: The particle size of the sulphoaluminate cement is 20-200 μm.

7. The quick-drying, anti-explosion, wear-resistant casting material according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin and phenol novolac epoxy resin; the mass ratio of the bisphenol A epoxy resin to the phenol novolac epoxy resin is (1~2):

1.

8. The quick-drying, anti-explosion, wear-resistant casting material according to claim 1, characterized in that: The water reducer is selected from any one of polycarboxylate water reducer, melamine water reducer and naphthalene water reducer or a combination of at least two thereof.

9. The quick-drying, anti-explosion, wear-resistant casting material according to claim 1, characterized in that: The defoaming agent is selected from any one of tributyl phosphate, polydimethylsiloxane, and tripolyglycerol monostearate, or a combination of at least two thereof.

10. A construction method for a quick-drying wear-resistant casting material that does not require drying and is resistant to bursting, characterized in that: The quick-drying wear-resistant casting material that does not require drying and is resistant to cracking as described in claims 1 to 9 is mixed with water, stirred evenly, and then spread on the construction surface and compacted, ground and polished.

Citation Information

Patent Citations

  • Pouring material and preparation method thereof, and fabricated pouring-molded large wall and preparation method thereof

    CN118684476A

  • Water-borne epoxy resin modified cement grouting material

    CN105503068A

  • Wear-resistant and antiknock concrete and preparation method thereof

    CN105801039A

  • Epoxy resin / cement mortar compound concrete material and preparation method therefor

    CN108546008A

  • Anti-crack corrosion-resistant ultra-high performance concrete with thixotropy and preparation method thereof

    CN115716734A